Halaju wang di Malaysia: bukti empirik - Abdul Karim, Zulkefly; Jusoh, Mansor; Khalid, Norlin (Universiti Utara Malaysia, 2010)
Purpose - This paper aims to examine the volatility of money velocity and also estimate the velocity of money function in Malaysia by using quarterly time series data. Design/Methodology/Approach - This study employed recent econometric techniques such as volatility model in ARCH and GARCH frameworks, Johansen co integration test, and Vector Error Correction Model (VECM). Findings - The results showed that the velocity of money for M1 (V1) and M2 (V2) are volatile and persistence rather than M3 (V3). The Johansen co-integration test result indicated that the existence of long-run relationships between velocity of money V1, V2 and V3 on the dependent variables, such as bond interest rate,deposit rate, and income. Furthermore, the VECM result showed that the changes in dependent variables such as bond interest rate, deposit rate, and income do significantly influence the changes in velocity of money for V2 and V3 in the long run. Conversely, in the short run, a change in the national income has only significantly caused changes in the velocity of money V2 and V3, while the interest rate is significant in causing the velocity of money V3. Originality/Value - This paper explores extensively the modern econometric techniques in investigating the issue of volatility and velocity of money in Malaysia. Paper type - Research paper.